Specialized interdisciplinary rehabilitation reduces persistent post-concussive symptoms: a randomized clinical trial. (23rd February 2019) - Rytter, Hana Mala; Westenbaek, Klaus; Henriksen, Henriette; Christiansen, Peter; Humle, Frank
ABSTRACT: Objective : To compare the effectiveness of a specialized, interdisciplinary rehabilitation (S-REHAB) with standard care (STAND) for people with persistent post-concussive symptoms (PPCS > 6 month). Design : Randomized controlled trial. Participants : Eighty-nine adults. Interventions : 22-week programme combining individual and group-based neuropsychological treatment with exercise therapy and physiotherapeutic coaching (S-REHAB), and the usual treatment offered by the public municipality services (STAND). Outcome Measures : The Rivermead Postconcussion Symptoms Questionnaire (RPSQ) (primary), The Headache Impact Test (HIT-6), Major Depression Inventory (MDI), Multidimensional Fatigue Inventory (MFI-20) and The Short Form (36) Health Survey (SF-36); all collected at baseline, post-treatment, and at 6-month follow-up. Results : The S-REHAB group showed a significant reduction in symptoms measured by RPSQ compared to the STAND immediately post-treatment (effect size [ES] = 0.28) and at follow-up (ES = 0.26). The S-REHAB groups also showed significant improvements regarding HIT-6 post-treatment (ES = 0.38) and at follow-up (ES = 0.68), MFI-20 – dimension 'mental fatigue' post-treatment (ES = 0.42), MFI-20 – dimension 'reduced activities' at follow-up (ES = 0.74) and SF-36 – dimension 'social functioning' post-treatment (ES = 0.31). Conclusions : The S-REHAB is more effective than the STAND in reducing the PPCS affecting physical, cognitive and emotional domains. This symptom reduction was associated with experienced improvement in social functioning, increased levels of activity, a decrease in mental fatigue and increased life satisfaction.